PENGARUH WORK FAMILY CONFLICT TERHADAP STRES KERJA DAN KOMITMEN ORGANISASIONAL PEGAWAI KONTRAK DINAS KEBUDAYAAN PROVINSI BALI - Krisna Divara, I Gusti Agung Gede; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen; Vol 5 No 11 (2016), 2016)
Organizational commitment is an important concept in the literature. Workers who have high organizational commitment will be more motivated to be involved in organization and achieving the goal of the organization. Worker who have low commitment tend to resign from their work place/company, this condition might happen because those who tend to resign from the job are usually not quite convenient with the workplace, do not have any intentions to achieve the goal of the organization, and have a really low work ethic. This research was done in Dinas Kebudayaan Provinsi Bali (Cultural Department of Bali Province). The respondents are consists of 53 employees. The data collection done by spreading the questionnaire using Likert scale. The analysis technique used path analysis. Based on the result of the analysis, it was found that work family conflict is significantly and positively influencing towards work stress. Work family conflict have significantly and negatively influencing towards organizational commitment. Work stress have significantly and negatively influencing towards organizational commitment. Work family conflict has an indirect influence towards organizational commitment, through work stress variable.
Keywords: work family conflict, work stress, organizational commitment